2012
DOI: 10.1161/circulationaha.111.063412
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inhibition of cGMP Phosphodiesterase 5A Improves Diabetic Cardiomyopathy

Abstract: Background-cGMP phosphodiesterase type 5 protein is upregulated in myocardial hypertrophy. However, it has never been ascertained whether phosphodiesterase type 5 inhibition exerts an antiremodeling effect in nonischemic heart disease in humans. We explored the cardioreparative properties of a selective phosphodiesterase type 5 inhibitor, sildenafil, in a model of diabetic cardiomyopathy. Methods and Results-Fifty-nine diabetic men (60.3Ϯ7.4 years) with cardiac magnetic resonance imaging consistent with nonisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 51 publications
3
93
0
4
Order By: Relevance
“…Data from the literature demonstrate an FMD improvement after chronic (13,24,25,26,27) and acute sildenafil administration in diabetic men (28). By using vardenafil, here, we demonstrate that FMD improves during treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Data from the literature demonstrate an FMD improvement after chronic (13,24,25,26,27) and acute sildenafil administration in diabetic men (28). By using vardenafil, here, we demonstrate that FMD improves during treatment.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, recent data have documented that long-term treatment with PDE5is might improve underlying organic comorbidities, providing a general health benefit although ED cure is not possible. [56][57][58] A drug ensuring a more natural profile of action and lower incidence of side effects could theoretically guarantee lower dropout, higher ED recovery, or successful improvement of ED (Box 2). Longer studies and head-tohead trials are advisable to better clarify these points.…”
Section: Expert Opinionmentioning
confidence: 99%
“…75 Giannetta et al reported anti-remodeling effects and improved cardiac kinetics from 3 months sildenafil treatment in diabetic cardiomyopathy patients. 76 These results suggest that PDE5 inhibition is a promising new approach to treating various human heart diseases. A large placebo-controlled multicenter trial (RELAX, NCT00763867) led by NIH is ongoing to test sildenafil efficacy in heart failure patients with preserved ejection fraction.…”
Section: Resultsmentioning
confidence: 96%